Utilization of Adobe Premiere Pro Using Project-Based Learning Strategies to Improve Learning Outcomes of Educational Technology Students in Broadcasting Technology Courses - Rivaldi, Muhammad Sultan Ari; Susanti Sufyadi; Sulistyo Rini (STKIP Al Islam Tunas Bangsa dan HEPI, 2025)
This study aims to describe the implementation strategy of Project-Based Learning (PBL) using Adobe Premiere Pro software and determine the impact of using this software on the academic results of Educational Technology students in the Broadcasting Technology course. The method used in this research is quantitative, with a descriptive quantitative approach, and data collection was carried out through observation, interviews, questionnaires, tests, and documentation. The results of this research show that the application of the Project-Based Learning (PjBL) model integrated with the use of Adobe Premiere Pro in broadcasting education has a positive and significant impact on students' academic results. Observation shows that the entire PjBL syntax was implemented effectively. The results of the pre-test and post-test analysis, using the Man Whitney U statistical test, show a statistically significant difference between the experimental group and the control group (p = 0.049 < 0.05). The survey responses show that most students felt helped and more interested in learning using Adobe Premiere Pro, with a response rate of 207.5% and the category “Very positive.” The results of the project evaluation show that the experimental class (Adobe Premiere Pro) obtained an average score of 84.24 (category “Good”), much higher than that of the control class (CapCut), with an average score of 60.58 (category “Fair”).